The Influence of Motivation, Work Discipline, and Compensation on Employee Performance - Sitopu, Yoel Brando; Sitinjak, Kevin Arianda; Marpaung, Feny Krisna (Manunggal Halim Jaya, 2021)
The study aims to know and analyze the effect of motivation, work discipline, and compensation on employee performance both partially and simultaneously. This research was carried out at PT. Sinar Jernih Suksesindo. The procedure starts from the trial of research instruments, data collection through questionnaires, conducting data analysis, and preparing research report results. The number of samples studied amounted to 130 employees. The data used in this study is the primary data that researchers obtain directly from the source. The result of this study states motivation, leadership and Compensation has significant effect on the employee performance with a sig value < 0.001. Factors that affect performance include work discipline, compensation, and motivation. Work discipline is needed to produce a good performance; with discipline, employees will try to do the work as much as possible, and the resulting performance will be better. Discipline must be enforced in an organization or company because without good employee discipline, and it is difficult for companies to realize their goals. The key to the company's success in achieving its goals is discipline. A discipline is a form of awareness or willingness of a person to obey all organizational or company regulations and applicable social norms.